2018
DOI: 10.1155/2018/7909684
|View full text |Cite
|
Sign up to set email alerts
|

How Visual Body Perception Influences Somatosensory Plasticity

Abstract: The study of somatosensory plasticity offers unique insights into the neuronal mechanisms that underlie human adaptive and maladaptive plasticity. So far, little attention has been paid on the specific influence of visual body perception on somatosensory plasticity and learning in humans. Here, we review evidence on how visual body perception induces changes in the functional architecture of the somatosensory system and discuss the specific influence the social environment has on tactile plasticity and learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 162 publications
(174 reference statements)
2
3
0
Order By: Relevance
“…Furthermore, reduced correlations between the somatosensory and visual network has been observed with increasing bulimia symptoms 67 . These findings taken along with our own suggest that the relationship between earlier onset of puberty and adult BMI may be related to increased sensory‐driven behaviours but decreased bodily perception 33,65,67 . Similarities between functional correlations in individuals who went through puberty early and disordered eating are in line with previous research demonstrating that being more developmentally advanced compared to one's peers is a risk factor for disordered eating in adolescence and adulthood, 68‐70 specifically for the clinical diagnosis of bulimia nervosa 71 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, reduced correlations between the somatosensory and visual network has been observed with increasing bulimia symptoms 67 . These findings taken along with our own suggest that the relationship between earlier onset of puberty and adult BMI may be related to increased sensory‐driven behaviours but decreased bodily perception 33,65,67 . Similarities between functional correlations in individuals who went through puberty early and disordered eating are in line with previous research demonstrating that being more developmentally advanced compared to one's peers is a risk factor for disordered eating in adolescence and adulthood, 68‐70 specifically for the clinical diagnosis of bulimia nervosa 71 .…”
Section: Discussionsupporting
confidence: 89%
“…67 These findings taken along with our own suggest that the relationship between earlier onset of puberty and adult BMI may be related to increased sensory-driven behaviours but decreased bodily perception. 33,65,67 Similarities between functional correlations in individuals who went through puberty early and disordered eating are in line with previous research demonstrating that being more developmentally advanced compared to one's peers is a risk factor for disordered eating in adolescence and adulthood, [68][69][70] specifically for the clinical diagnosis of bulimia nervosa. 71 Similar retrospective research shows that adult women who reported going through puberty earlier than their peers were more dissatisfied with the physical changes accompanying pubertal development and this predicted eating disorder symptoms.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Activation of V1 during deviancy processing in the Pla compared with Psi condition may reflect the impact of visual processing on tactile perception (Kuehn and Pleger 2018). Vision can exert a top-down influence on the integration and localization of tactile information.…”
Section: Psi Reduces the Bold Signal In Frontal And Visual Areas In Response Tactile Surprising Stimulimentioning
confidence: 97%